Teach like a queen : lessons in leadership from great contemporary women - Leese, Tracey; Barker, Christopher; Brown, Lauren (New York : Routledge, 2022)
"This exciting and unique text brings together leadership theory, popular culture and action research to inspire and empower female teachers into leadership roles. Teach Like a Queen celebrates the successes of iconic women and translates their respective brilliance into becoming successful, dynamic, and high-performing practitioners and educational leaders. Focusing on seven key inspirational women as archetypes, the authors address emerging professional issues which will benefit classroom practitioners and leaders, each correlating to a different Nolan principle and inspirational queen. Inspired by the incredible work of #WomenEd, including a Foreword from Vivienne Porritt, each lesson features: a constructed definition of each respective icon and how that translates into the teaching profession; a case study exploring how a female school leader experienced her own Queen moment and the leadership lesson it taught her key lessons for aspiring leaders; takeaway actions to channel your inner queen Illustrating how a diverse cross-section of women personify the leadership strength of their assigned principle in practice, Teach Like a Queen will empower female teachers to aspire to lead and equip them with practical strategies to secure and fulfil leadership roles"--
Foreword / Vivienne Porritt of #WomenEd -- Preface: (Ladies and) the Lake -- Introduction: The Nolans in principle and practice -- Queen I and Openness: Michelle Obama -- Queen II and Honesty: RuPaul -- Queen III and Objectivity: Meghan Markle -- Queen IV and Selflessness: Lady Gaga -- Queen V and Integrity: Jacinda Ardern -- Queen VI and Accountability: Kim Kardashian-West -- Queen VII and Leadership: Malala -- Happily, ever after.
Keywords: Women school administrators; Educational leadership; Feminism and education; School management and organization; Women educators; EDUCATION -- Leadership; EDUCATION -- Secondary; EDUCATION -- Elementary